Study of the thermal behavior in oxidative and pyrolysis conditions of some transition metals complexes with Lornoxicam as ligand using the techniques: TG-DSC, DSC, HSM and EGA (TG-FTIR and HSM-MS) - Zangaro, Georgia A. C. [UNESP] (2019)
Lornoxicam metal complexes [M(Lor)(2)(OH2)(2)]center dot nH(2)O, where M represents the bivalent transition metals (Mn(II) to Zn(II)), Lor is Lornoxicam ligand and n = 2.0 or 2.5 were synthesized. The compounds were characterized by elemental analysis (EA), powder X-ray diffraction (PXRD), infrared spectroscopy (FTIR), simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC) under oxidizing and pyrolysis conditions, differential scanning calorimetry (DSC), hot-stage microscopy (HSM) and evolved gas analysis (EGA) by coupled hot-stage microscopy (HSM-MS) and Fourier transform infrared (TG-FTIR). Regardless of the atmosphere, the thermal stability and thermal behavior up to the first two mass loss steps of the anhydrous compound were similar, only differing significantly in the last steps. The main gaseous products released were H2O (dehydration), SO2, CO, CO2, COS, HCN, HNCO, Methyl Isocyanate, and Ethyl Isocyanate. In addition, FTIR data suggest that pyridyl and carboxyl groups are the coordination sites for metal ions and confirm the presence of differing bounded waters.